Factors Influencing the Purchase Intention of Basmati Rice in Chittoor District of Andhra Pradesh - Priyanka , Aparna , Prabhavathi and Lavanyakumari (Indian Journal of Extension Education, 2018)
Basmati rice is unique among other aromatic long grain rice varieties. Agro-climatic conditions of thespecific geographical area, as well as method of harvesting, processing and aging, attribute thesecharacteristic features to basmati rice. This paper made a humble attempt to understand the factors influencingthe purchase intention of basmati rice in Chittoor district of Andhra Pradesh. Major retailers in the districtwere identified and five retailers were randomly chosen for the study. Thirty consumers visiting each retailshop were identified and randomly selected; the total sample size is 150. The collected data was analysedby using Likert scale and factor analysis. Seasoning factor was the most considered factor for purchase thebasmati rice.